Does cumulative topical antibiotic powder use increase the risk of drug induced acute kidney injury in fracture patients?. (2022) - O'Hara, N. N.; Carullo, J.; Joshi, M.; Banoub, M.; Claeys, K. C.; Sprague, S.; Slobogean, G. P.; O'Toole, R. V.
No abstract available